Faktor-Faktor Yang Mempengaruhi Permintaan Keripik Pisang Sale (Studi Kasus : UMKM KUB Keripik Pisang Sale di Desa Teratak Perkebunan Sei Bejangkar) - Sari, Ricca Novita; Napitupulu, Safrida (Universitas Medan Area, 2023)
Demand is a person's needs and desires for goods and services at various times at various price levels. Demand is a process of requesting something or a number of goods to be purchased or requested at a certain price and time. Demand is influenced by several factors, namely taste, price and quality. In this research, the author wants to discuss the factors that influence the demand for sale banana chips in Teratak Perkebunan Sei Bejangkar Village and how these factors influence the demand for sale banana chips in Teratak Perkebunan Sei Bejangkar Village. In this research the author used a quantitative descriptive method with a questionnaire instrument. This research explains the factors that influence the demand for sale banana chips and how these factors influence the demand for sale banana chips. In this research, the results showed that taste, price and quality significantly influence the demand for sale banana chips in Teratak Perkebunan Sei Bejangkar Village. Price is a factor that has a greater influence than taste and quality on the demand for sale banana chips in Teratak Perkebunan Sei Bejangkar Village.